If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(3x + -9) = 8(-8 + -1x) Reorder the terms: -4(-9 + 3x) = 8(-8 + -1x) (-9 * -4 + 3x * -4) = 8(-8 + -1x) (36 + -12x) = 8(-8 + -1x) 36 + -12x = (-8 * 8 + -1x * 8) 36 + -12x = (-64 + -8x) Solving 36 + -12x = -64 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 36 + -12x + 8x = -64 + -8x + 8x Combine like terms: -12x + 8x = -4x 36 + -4x = -64 + -8x + 8x Combine like terms: -8x + 8x = 0 36 + -4x = -64 + 0 36 + -4x = -64 Add '-36' to each side of the equation. 36 + -36 + -4x = -64 + -36 Combine like terms: 36 + -36 = 0 0 + -4x = -64 + -36 -4x = -64 + -36 Combine like terms: -64 + -36 = -100 -4x = -100 Divide each side by '-4'. x = 25 Simplifying x = 25
| (-5x)+(-215)-(5x)+(21.5)= | | 3(3x-3)+2x=0 | | $200,000-1/10 | | 12-x=-38 | | 7x+4=4x+2 | | 9(-7)+8y=17 | | X+9y=-26 | | 2(x+4)=88 | | 3k+18=k+18 | | 168+8y=7x | | -34=v+5v-42 | | 18z+-14z-8=-30-6 | | 6x+4(2x+13)=136 | | -6(1-7n)=34+2n | | m/30=10/3 | | 1.5n=9 | | 2(7)+10y=-6 | | 3(h+7)=-18 | | (1/8)^2-2n=16 | | 2/s=7/9 | | 4cos^2(x)+2=5 | | 5x+2y=2x+4y | | 6(2x+8)-9x=0 | | 1.5(b+2)+3b=-1 | | x+x*6.2=180 | | B+4b=15 | | 41.4/5.03 | | x^2+x-11=13-x | | r/18-4=2 | | h=-8.5t^2+10t | | 8m-5=4m-13 | | 34-(1/2)x7 |